Inflammation and Mood Disorders: Proinflammatory Cytokines and the Pathogenesis of Depression - Beatriz Currier, M.; B. Nemeroff, Charles (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2010)
Increasing evidence suggests that activation of the innate immune system may play a seminal role in the pathophysiology of depression. Several lines of evidence support the association of inflammation and depression. Peripheral administration of cytokines, such as interferon-alpha, can induce many of the symptoms of the depressive syndrome. In addition, medically healthy patients with major depression exhibit elevated plasma levels of proinflammatory cytokines. Moreover, cytokines produce effects on a variety of neurobiological substrates previously implicated in the pathogenesis of depression. Thus, proinflammatory cytokines alter neuroendocrine function, several neurotransmitter systems including dopamine and glutamate, neural plasticity, and neuronal activity in limbic regions. The burgeoning evidence that depression is an inflammatory disease is reviewed.
Keywords: Inflammation